Can Cypriot physical education teachers fully embrace physical literacy? An initial exploratory sequential study - Christodoulides, Efstathios; Grecic, David; Tsivitanidou, Olia; Sprake, Andrew (Frontiers in Education, 2025)
IntroductionThe purpose of this project was to explore whether Cypriot Physical Education (PE) teachers can fully embrace Physical Literacy (PL) and to determine the contributory factors.MethodsAn exploratory sequential mixed methods design collected data from 135 Cypriot PE teachers utilizing the Teacher Change Questionnaire—Physical Education (TCQ-PE) and the Perceived Physical Literacy Instrument (PPLI) questionnaires. Follow-up semi-structured interviews were conducted and thematically analyzed (n = 6).ResultsFindings revealed that only 23% of teachers demonstrated a willingness to change current practice. Most had generally high levels of the PPLI Knowledge construct (M = 4.59; SD = 0.08) but interviews found that actual self-reported knowledge was limited especially in relation to their awareness of PL’s basis, its identification and aligned teaching behaviors. Key barriers and enablers to PL adoption were described and practical recommendations made.DiscussionIn conclusion the study identifies that both Top-down and bottom-up strategies are required with aligned professional development for PL to be embedded in Cyprus’ Physical Education classes and achieve its health benefits for children.